2021
DOI: 10.1097/tin.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Role of Thiamine Supplementation in Treatment of Refeeding Syndrome

Abstract: The purpose of this systematic review is to identify studies where measurable thiamine supplementation was provided to patients at risk for or with refeeding syndrome to improve treatment guidelines. A systematic review of PubMed and CINAHL Plus databases was conducted using the terms refeeding syndrome, hypophosphatemia, thiamine, and vitamin B1. A total of 173 articles were retrieved and 11 case studies and 1 retrospective study met inclusion criteria. All studies identified symptoms of thiamine deficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The conditions that may generate deficiency are numerous [37]. The Wernicke-Korsackoff syndrome or symptoms are among the extreme manifestations, but delirium, congestive heart failure and oedema may be the presentation form [38]. A study in paediatric ICUs showed that the prevalence of thiamine deficiency based on blood levels is elevated by 11.1% and low levels may persist for 2--3 days [39].…”
Section: Thiamine B1mentioning
confidence: 99%
“…The conditions that may generate deficiency are numerous [37]. The Wernicke-Korsackoff syndrome or symptoms are among the extreme manifestations, but delirium, congestive heart failure and oedema may be the presentation form [38]. A study in paediatric ICUs showed that the prevalence of thiamine deficiency based on blood levels is elevated by 11.1% and low levels may persist for 2--3 days [39].…”
Section: Thiamine B1mentioning
confidence: 99%
“…Although all vitamin deficiencies can occur to varying degrees with inadequate intake, thiamine is of paramount importance when post-meal complications are considered. Thiamine is an essential coenzyme in carbohydrate metabolism and acts as the main cofactor of pyruvate dehydrogenases in glycolysis ( 49 ). Thiamine deficiency can lead to encephalopathy-like symptoms such as ataxia, eye disorders, amnesia, and coma in these patients ( 46 ).…”
Section: Pathophysiology and Clinical Manifestationsmentioning
confidence: 99%